Acute Anemia and Intracranial Hypertension - A case report - Silva, Marilia Fontenelle e; Murta, Nina Rosa Aparecida Felisardo; Moraes, Helena Providelli de; Gomez, Rodrigo Santiago; Assunção, Pablo Augusto Silva de (Headache Medicine, 2023)
Full abstract in PDF.